2021
DOI: 10.3233/adr-210005
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen Years of the Australian Imaging, Biomarkers and Lifestyle (AIBL) Study: Progress and Observations from 2,359 Older Adults Spanning the Spectrum from Cognitive Normality to Alzheimer’s Disease

Abstract: Background: The Australian Imaging, Biomarkers and Lifestyle (AIBL) Study commenced in 2006 as a prospective study of 1,112 individuals (768 cognitively normal (CN), 133 with mild cognitive impairment (MCI), and 211 with Alzheimer’s disease dementia (AD)) as an ‘Inception cohort’ who underwent detailed ssessments every 18 months. Over the past decade, an additional 1247 subjects have been added as an ‘Enrichment cohort’ (as of 10 April 2019). Objective: Here we provide an overview of these Inception and Enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 125 publications
2
88
0
Order By: Relevance
“…The p-tau181/Aβ 1-42 ratio has long been considered to have the best statistical power of the CSF markers for representing AD, as it incorporates both hallmarks of the AD disease pathway and represents a later stage of the disease pathway. Indeed this ratio in CSF has helped identify late stage changes in synaptic and neuronal degradation markers and inflammatory markers associated with AD [37], as well as show high concordance with Aβ-PET [15-17, 20]. Here analyses of the plasma markers at a second time point in this study showed increased performance of all markers, including the p-tau181/Aβ 1-42 ratio, at predicting amyloid status at Assessment 2, which may reflect further accumulation of positive biomarker signals compared to a static baseline in the amyloid negative cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p-tau181/Aβ 1-42 ratio has long been considered to have the best statistical power of the CSF markers for representing AD, as it incorporates both hallmarks of the AD disease pathway and represents a later stage of the disease pathway. Indeed this ratio in CSF has helped identify late stage changes in synaptic and neuronal degradation markers and inflammatory markers associated with AD [37], as well as show high concordance with Aβ-PET [15-17, 20]. Here analyses of the plasma markers at a second time point in this study showed increased performance of all markers, including the p-tau181/Aβ 1-42 ratio, at predicting amyloid status at Assessment 2, which may reflect further accumulation of positive biomarker signals compared to a static baseline in the amyloid negative cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The Australian Imaging, Biomarkers and Lifestyle (AIBL) study is a prospective longitudinal cohort of adults over the age of 60 designed to understand the natural history of AD, with recruitment and testing procedures described in detail [20]. Participants undergo 18 monthly neuropsychological and clinical assessment and blood donation, with AIBL clinical classification confirmed by an expert clinical panel consisting of a neurologist, geriatrician, and neuropsychologist; all blinded to biomarker status.…”
Section: Methodsmentioning
confidence: 99%
“…Participants in this study were older adults (aged 50 years and over) enrolled in the Australian Imaging Biomarkers and Lifestyle (AIBL) Study, a prospective longitudinal cohort study of aging and AD [ 12 ]. Individuals from this cohort who did not have a mild cognitive impairment or dementia diagnosis underwent positron emission tomography (PET) imaging, had an objective audiometric assessment of their hearing within 5 years of their scans, had cognitive assessment within 2 years of their PET scan, and had no diagnosed mild cognitive impairment or dementia were selected ( n = 143).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were deemed to be cognitively unimpaired (CU) if their performance on neuropsychology assessments was within 1.5 standard deviations of published normative data for their age group. A diagnosis of mild cognitive impairment (MCI) or Alzheimer’s disease dementia (AD) was assigned in accordance with international consensus criteria, as previously described (16). This study has been approved by the institutional review boards of all participating institutions, and all participants signed an informed consent form.…”
Section: Methodsmentioning
confidence: 99%